ANALISA POLA SPASIAL TERMINAL PENUMPANG GAPURA SURYA NUSANTARA PELABUHAN TANJUNG PERAK SURABAYA - Andini, Dewanti (Unika Santo Thomas, 2022)
Gapura Surya Nusantara Passenger Terminal in the Tanjung Perak Port area of Surabaya. The location is on Jalan Tanjung Perak, North Perak, Kec. Beautiful Customs, Surabaya. This port is an industrial, trade and service area, in the form of a cargo terminal and a passenger terminal. The purpose of this study is to analyze the state of the building including the relationship between circulation patterns and space. The arrangement of the inner area uses a linear pattern. This pattern facilitates the flow of activities in the process of moving between modes of transportation. The spatial arrangement of the building is in accordance with the functional space design and the arrangement of static space elements. This building consists of three floors. Floor arrangement is distinguished according to the urgency of the building. The first and second floors are service areas, but the second floor also has a management area. The third floor is focused on commercial areas as public spaces and hospitality areas. The results of the analysis of spatial and land use patterns are expected to improve the quality of being a guide for other port passenger terminals in Indonesia so that land use and spatial patterns are in accordance with established standards.